2008
DOI: 10.1038/cr.2008.37
|View full text |Cite
|
Sign up to set email alerts
|

The roles of MAPKs in disease

Abstract: MAP kinases transduce signals that are involved in a multitude of cellular pathways and functions in response to a variety of ligands and cell stimuli. Aberrant or inappropriate functions of MAPKs have now been identified in diseases ranging from cancer to inflammatory disease to obesity and diabetes. In many cell types, the MAPKs ERK1/2 are linked to cell proliferation. ERK1/2 are thought to play a role in some cancers, because mutations in Ras and B-Raf, which can activate the ERK1/2 cascade, are found in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
131
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(141 citation statements)
references
References 91 publications
(99 reference statements)
0
131
0
6
Order By: Relevance
“…The phosphorylation of ERK is associated with cell proliferation and cell migration through effects on cell-matrix contacts. 46 It was also reported to be found in Müller-glial cells after RD. 47 Taken together, our results suggest that extracellular HMGB1 from dying ocular cells might affect retinal cells through ERK phosphorylation and potentially serve to promote the formation of PVR, which is wound healing, but has a pathological meaning in the eye.…”
Section: Hmgb1 In Retinal Detachment N Arimura Et Almentioning
confidence: 98%
“…The phosphorylation of ERK is associated with cell proliferation and cell migration through effects on cell-matrix contacts. 46 It was also reported to be found in Müller-glial cells after RD. 47 Taken together, our results suggest that extracellular HMGB1 from dying ocular cells might affect retinal cells through ERK phosphorylation and potentially serve to promote the formation of PVR, which is wound healing, but has a pathological meaning in the eye.…”
Section: Hmgb1 In Retinal Detachment N Arimura Et Almentioning
confidence: 98%
“…It is known that Ras and associated signaling cascade is експериментальні роботи able to activate NF-κB, especially in tumor cells [21], but the reverse effect of factor on this cascade was studied insufficiently. One of possible mechanisms of this activation can be a release of protein kinase TLP2 from the complex, consisting of MAPK/p105-subunit of NF-κB/TLP2 [22].…”
Section: Fig2theeffectofthecombinedactionofpaclitaxelandnf-κbinhibimentioning
confidence: 99%
“…It has been reported that Gi/o proteins, which are known to affect a variety of cellular functions, activate p-ERK1/2 and subsequent cell proliferation signals [10,32]. AA metabolites are also able to induce cell growth and have been strongly implicated in tumor development [38,39].…”
Section: -Test)mentioning
confidence: 99%
“…Activation of the MAPK cascade is necessary for cell growth and proliferation [10]. The MAPK family serves as a convergence point for intracellular signal transduction pathways (including coupling HBx cytoplasmic signaling to its gene expression program) and functions as a mediator of cel-lular responses to a variety of cellular stimuli [11,12].…”
Section: Introductionmentioning
confidence: 99%